2017
DOI: 10.1155/2017/7091904
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Alleviates the Endothelial Dysfunction Induced by Hydrogen Peroxide in Rat Aortic Rings via Activation of AMPK

Abstract: Endothelial dysfunction is the key player in the development and progression of vascular events. Oxidative stress is involved in endothelial injury. Rosmarinic acid (RA) is a natural polyphenol with antioxidative, antiapoptotic, and anti-inflammatory properties. The present study investigates the protective effect of RA on endothelial dysfunction induced by hydrogen peroxide (H2O2). Compared with endothelium-denuded aortic rings, the endothelium significantly alleviated the decrease of vasoconstrictive reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Accumulating evidence obtained from in vitro, in vivo, and clinical studies supports the free radical scavenging properties of natural phenolic antioxidants [24]. In this study, we proposed that natural herbal phenolic compounds with strong antioxidant activity, such as rosmarinic acid [24] and carvacrol [29], could help to counteract the toxicity of Al.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Accumulating evidence obtained from in vitro, in vivo, and clinical studies supports the free radical scavenging properties of natural phenolic antioxidants [24]. In this study, we proposed that natural herbal phenolic compounds with strong antioxidant activity, such as rosmarinic acid [24] and carvacrol [29], could help to counteract the toxicity of Al.…”
Section: Discussionmentioning
confidence: 74%
“…Elevated Al 3+ concentrations lead to Al 3+ -induced formation of oxygen radicals causing lipid peroxidation, which results in cell membrane damage and oxidative stress [3][4][5][6][7]. Accumulating evidence obtained from in vitro, in vivo, and clinical studies supports the free radical scavenging properties of natural phenolic antioxidants [24]. In this study, we proposed that natural herbal phenolic compounds with strong antioxidant activity, such as rosmarinic acid [24] and carvacrol [29], could help to counteract the toxicity of Al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KG-501 is a small molecule inhibitor of cyclic AMP response element (CRE)-binding protein (CREB) ( Sun et al, 2008 ), and TrkB-Fc chimeric protein serves as a BDNF scavenger ( Huang et al, 2010 ). The inhibitor concentrations were referenced in previous studies ( Helan et al, 2014 ; Kang et al, 2014 ; Zhou et al, 2017 ). According to the manufacturer’s instructions, metformin, D -glucose, and TrkB-Fc were dissolved in sterile PBS, and CC and KG-501 were dissolved in dimethylsulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…However, concurrent treatment with ethyl rosmarinate was shown to prevent this alteration. Other studies have shown that the parent compound of ethyl rosmarinate, rosmarinic acid, caused vasodilatory effects regulated through the endothelium-dependent pathway and against endothelial dysfunction through the 5ʹ adenosine monophosphate-activated protein kinase (AMPK)/eNOS pathway [16,22]. From the results of this study, it can be proposed that ethyl rosmarinate prevented hypertension through the up-regulation of the eNOS signaling pathway.…”
Section: Discussionmentioning
confidence: 57%